DEVELOPMENT OF AN ALGORITHM FOR ESP32-CAM OPERATION IN HTTP SERVER MODE FOR STREAMING VIDEO - Yevsieiev , Vladyslav; Maksymova, Svitlana; Starodubcev, Nikolaj (Collection of scientific papers «ΛΌГOΣ», 2022)
One of the key factors in mobile robots development is the choice and implementation of the control system [1]. Analyzing publications on the development of portable or small-sized mobile robots for solving specialized or point tasks, it was found that many authors use the concept of the Internet of Things (IoT) to implement a control system and computer vision [2]. The works of Azis Isrofi, Shoffin Nahwa Utama and Rishabh Chauhan show a mobile robot control system implementation example based on ESP32-Cam [3,4]. Unfortunately, the authors use an external mobile device with the function of creating a Wi-Fi point to control a mobile robot, which is not always acceptable. The authors LIM, Myung-Jae and Lalu Fatwa Aulia in their research analyze IoT technology algorithms for implementing work with miniature mobile robots [5,6]. But the authors do not show how they implement the control system and operator connection. Based on the analysis carried out in this research, an algorithm for dynamic connection to a mobile robot control system based on ESP32-CAM was developed, it is shown in Figure 1.